Systematic Review of the Participation of the Disabled in Physical Education Class - Sevim Akşit; Emine Büşra Yılmaz; Bülent Ağbuğa (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to provide suggestions for eliminating the existing problems by systematically reviewing the studies on the curricula established on the basis of the participation of students with special needs in physical education classes and the inclusion of these students in the lesson. In this direction, the literature was searched through an online search engine for the research. Accordingly, three databases named Academic Search Complete, Sport DISCUSS and ERIC were searched. 22 articles selected according to the Prisma method of Moher et al. (2009) were included in the study and articles that met the determined criteria were analyzed using the continuous comparative analysis technique. According to the results the problems experienced by the students with special needs are generally due to socialization with their peers in the school environment, especially within the scope of physical education lessons, equipment, school - architectural structure, teacher and curriculum. The solution to these problems depends on meeting the educational and physical activity needs of students with special needs, being together with their peers and society, meeting their own needs and increasing their ability to live without being dependent on others as much as possible. The most suitable environment for these to be achieved is the school environment, where disabled people first meet with other individuals, unlike their family members. For this, first of all, the needs of students with special needs should be determined. In this regard, teacher training programs of universities should be expanded. In addition, the cooperation of the teacher, counselor, school psychologist and family is important.